Antenna Miniaturization with MEMS Tunable Capacitors: Techniques and Trade-Offs - Samantha Caporal Del Barrio; Art Morris; Gert F. Pedersen (International Journal of Antennas and Propagation)
In today’s mobile device market, there is a strong need for efficient antenna miniaturization. Tunable antennas are a very promising way to reduce antenna volume while enlarging its operating bandwidth. MEMS tunable capacitors are state-of-the-art in terms of insertion loss. Their characteristics are used in this investigation. This paper uses field simulations to highlight the trade-offs between the design of the tuner and the design of the antenna, especially the impact of the location of the tuner and the degree of miniaturization. Codesigning the tuner and the antenna is essential to optimize radiated performance.